2021
DOI: 10.3390/jof7060472
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Potential of Bacillus amyloliquefaciens against Botrytis pelargonii and Alternaria alternata on Capsicum annuum

Abstract: The aim of this study was to assess the ability of Bacillus amyloliquefaciens, to augment plant growth and suppress gray mold and leaf spot in pepper plants. Morphological modifications in fungal pathogen hyphae that expanded toward the PGPR colonies were detected via scanning electron microscope. Furthermore, preliminary screening showed that PGPR could produce various hydrolytic enzymes in its media. Treatments with B. amyloliquefaciens suppressed Botrytis gray mold and Alternaria leaf spot diseases on peppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 129 publications
1
12
0
Order By: Relevance
“…Also, our data was consistent with previous studies that the fungal and bacterial communities suppress pathogens via multiple mechanisms 46 , such as direct inhibition, secretion of antimicrobial substances 6,47,48 , activation of the systemic immune response 49 , and biofilm formation in the rhizosphere. Taken together, the different roles of bacteria and fungi in the activation of the tomato innate immune systems, nutrient/niches competition, and secretion of fungicide compounds highlighted the irreplaceable functional roles of Bac and Fun SynComs 34,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, our data was consistent with previous studies that the fungal and bacterial communities suppress pathogens via multiple mechanisms 46 , such as direct inhibition, secretion of antimicrobial substances 6,47,48 , activation of the systemic immune response 49 , and biofilm formation in the rhizosphere. Taken together, the different roles of bacteria and fungi in the activation of the tomato innate immune systems, nutrient/niches competition, and secretion of fungicide compounds highlighted the irreplaceable functional roles of Bac and Fun SynComs 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-one CAZ-associated pathways were enriched (FDR-adjusted P < 0.05) in CrossK SynComs compared to the CAZassociated pathways in Bac SynComs and Fun SynComs, such as chitinase, xyloglucan hydrolase, chitin-binding protein, pectin methylesterase, mannan-binding, endoglucanase, cellulases, and lipases (Supplementary Data 19). These enzymes may inhibit the growth of FOL, thereby supporting tomato resistance against FOL and enhancing the survival of tomato plant 34,35 .…”
Section: Tomato Immune Responses Triggered By Different Syncomsmentioning
confidence: 99%
“…The enhancing capacity of B. amyloliquefaciens for pepper plant growth is in coherence with Shahzad et al [ 85 ] and Rashad et al [ 19 ], who documented that B. amyloliquefaciens RWL-1 and GGA inoculation significantly enhanced the growth traits of tomato and garlic plants under both diseased and non-diseased conditions of F. oxysporum and S. cepivorum . The extensively distinguished mechanisms for plant growth promotion caused by B. amyloliquefaciens are through phytohormones, providing the essential nutrients, N 2 fixation, and phosphate solubilization [ 18 ]. In addition, endophytic bacteria may promote plant growth through biofertilization [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amaresan et al [ 16 ] found that endophytic bacteria that were isolated from Capsicum annuum have an antagonistic effect against several phytopathogens. Also, infection by fungal pathogens results in stronger reductions in plant biomass and survival compared to uninfected plants [ 12 , 18 , 19 ]. Bacillus was mentioned in numerous research papers due to its prevalence in many plants, its antibacterial properties [ 20 , 21 , 22 ], and its ability to produce endospores that are UV, pH, temperature, and salinity resistant [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…are the most used BCAs and appear to be effective in a wide range of pathosystems [92]. Recently, Ramírez-Cariño et al [93] and Kazerooni et al [94] reported that tomato early blight and pepper leaf spot, caused by Alternaria alternata, can be controlled by Bacillus spp. protecting plants from pathogen attack through induction of systemic resistance in the host.…”
Section: Bcas Against Air-borne Pathogensmentioning
confidence: 99%